2011
DOI: 10.1515/ijdhd.2011.057
|View full text |Cite
|
Sign up to set email alerts
|

A virtual reality approach to gait training in service members with lower extremity amputations

Abstract: Gait training is an essential part of the rehabilitation process for those with lower extremity (LE) amputations. For service members at Walter Reed Army Medical Center, the Computer Assisted Rehabilitation Environment (CAREN) allows virtual reality to be incorporated into gait training as an adjunct to conventional therapies. This retrospective case series examines the self-selected velocities achieved in two different virtual environments (VE) by 11 service members with LE amputations. These VEs allowed part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Twenty-two articles used the computer-assisted rehabilitation environment system for biomechanical analysis , 15 articles used the computerassisted rehabilitation environment system for rehabilitation [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57], 4 articles were reviews [19,20,58,59] and 9 articles addressed the computerassisted rehabilitation environment system in other ways [60][61][62][63][64][65][66][67][68]. A flow chart summarizing study selection is shown in figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty-two articles used the computer-assisted rehabilitation environment system for biomechanical analysis , 15 articles used the computerassisted rehabilitation environment system for rehabilitation [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57], 4 articles were reviews [19,20,58,59] and 9 articles addressed the computerassisted rehabilitation environment system in other ways [60][61][62][63][64][65][66][67][68]. A flow chart summarizing study selection is shown in figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…The computer-assisted rehabilitation environment system was used in different types of rehabilitation: neurological [43][44][45][46] vestibular [47][48][49][50], psychological [51,52], amputation [53], Cognitive [54] and visual rehabilitation [55]. We also identified two randomized controlled trial protocols: one was for the use of the computer-assisted rehabilitation environment system in improving balance and reducing falls in older adults [56] and the other was for the use of the computer-assisted rehabilitation environment system in military members with combat-related treatment-resistant posttraumatic stress disorder [57].…”
Section: Figure 1 Flow Chart Summarizing Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports including biomechanics measurements indicate that the CAREN is a successful tool to rehabilitate and train individuals with lower extremity injuries over multi-week rehabilitation programs. Several studies [18][19][20][21][22] examined the use of the CAREN as an adjunct to conventional physical therapy for active duty persons with lower limb amputations to work on dynamic weight shifting and gait. They found improved performance over several weeks of training, though the type of improvements varied between studies.…”
Section: Injured Population Focused On Rehabilitation Techniquesmentioning
confidence: 99%
“…They found improved performance over several weeks of training, though the type of improvements varied between studies. Studies by Kruger [19,20] reported increased selfselected walking velocities, decreased step width, improvements in overall stride symmetry, and ability to negotiate inclines and declines. Darter and Wilken [21] did not report the same improvements in temporal spatial parameters, but saw certain kinematic improvements (i.e.…”
Section: Injured Population Focused On Rehabilitation Techniquesmentioning
confidence: 99%